Protective efficacy of pirfenidone in rats with pulmonary fibrosis induced by bleomycin - Gul, Sule; Cörtük, Mustafa; Akanıl Fener, Neslihan; Yavuzsan, Eminegül; Eren, Ramazan; Baydili, Kursad Nuri; Çekmen, Mustafa Baki; Cetinkaya, Erdogan (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2023)
Background: Bleomycin causes increased production of reactive oxygen species, leads to pulmonary toxicity, fibroblast activation, and fibrosis. Objectives: This study aimed to evaluate the protective effect of pirfenidone on bleomycin-induced lung toxicity in rats. Methods: Twenty-eight adult rats were randomly divided into 3 groups; Bleomycin (B group, n=10), Bleomycin and Pirfenidone (B-PND group, n=13), and the control group (n=5). The bleomycin regimen was administered for 9 weeks. Pirfenidone was administered at 100 mg/kg daily. Total antioxidant level (TAS), total oxidant level (TOS), tumor necrosis factor (TNF-α), transforming growth factor (TGF-β1), matrix metalloproteinase-2 (MMP-2), plasminogen activator inhibitor (PAI) levels were studied. Histopathologically, sections were stained with Hematoxylin-eosin and Masson-trichrome for grading-scoring according to the Ashcroft score. Results: Stage 3 fibrosis was observed in 50% of the B group rats, stage 3 and higher fibrosis was never detected in the B-PND group and the difference was statistically significant (p=0.003). When evaluating tissue inflammation, the inflammation was higher in the B-PND group than in the other groups (p<0.001). Pleuritis was detected in all rats in group B, while was not observed in B-PND and control group (p<0.001). The TAS level was found to be significantly higher in group B than in group B-PND (p=0.034), while no difference was found between TOS, TNF-α, MMP-2, PAI, TGF-β1. Conclusions: Pirfenidone had a statistically significant protective effect in bleomycin-induced lung fibrosis and pleuritis in rats. Despite the presence of inflammation in the tissue, no significant changes were observed in inflammation markers in the peripheral blood. Novel serum biomarkers are needed to indicate the presence of inflammation and fibrosis in the lung.